Prevalence and hepatic histopathological findings of fascioliasis in sheep slaughtered in Jeddah, Saudi Arabia - Safinaz J. Ashoor; Majed H. Wakid (Scientific Reports, 2023)
Abstract Hepatic fascioliasis is an important parasitic disease responsible for morbidity and mortality in many domestic ruminants, especially sheep, goats, and cattle, due to Fasciola (F.) hepatica and F. gigantica. This study aimed to determine the prevalence of fascioliasis in sheep slaughtered in Jeddah, Saudi Arabia, and to describe the morphological and histopathological changes in the liver. A total of 109,253 sheep slaughtered between July 2017 and July 2018 were screened to assess the prevalence of fascioliasis. The livers were grossly investigated for Fasciola infection and morphological changes. Tissue samples were collected for proper histopathological examinations. Livers of local and imported sheep represented infection rates of 0.67% and 2.12%, respectively, and the highest infection rate was in the spring season. Macroscopically, the affected liver showed hepatomegaly, thickened capsule and discoloration with necrosis, fibrosis, dilation of the bile duct, engorgement of the gallbladder and enlargement of the portal lymph nodes. Microscopic examination showed fibrotic thickening, calcification and hyperplasia of the bile ducts filled with debris, as well as massive hemorrhagic foci. Histopathological examinations of the infected liver showed a central vein region with disturbed parenchyma cells, focal lymphocytic infiltration, elongated endothelial cells, blood sinusoids that showed enlarged Kupffer cells, patches of lysed or necrotic hepatocytes, eosinophil infiltration, lymphocytes and proliferating fibroblast, thickening of hepatic artery and arteriolar walls. We concluded that fascioliasis among sheep slaughtered in Jeddah is not uncommon. The identified histopathological changes in the liver of infected sheep reflect tissue damage, which can lead to significant economic losses for the animals.